The Importance of WE in POWER: Integrating Police Wellness and Ethics - Blumberg, Daniel M.; Papazoglou, Konstantinos; Schlosser, Michael D. (Frontiers in Psychology, 2020)
In this article, the authors introduce the POWER perspective of police wellness and ethics. POWER stands for Police Officer Wellness, Ethics, and Resilience. The perspective represents the view that wellness and ethics cannot be discussed separately; they are inextricably connected to each other. Initiatives to address one should always, simultaneously, include the other. Although there is a need for wellness and ethics to be addressed on an organizational level (Blumberg, Papazoglou, & Schlosser, under review; Thoen et al., 2020), the present article emphasizes the importance of POWER for individual police officers. The authors make the argument that officers need to expand the way in which they conceptualize their own wellness to include efforts to maintain ethical decision-making. Specifically, officers will remain psychologically healthier when they take active steps to stay steadfastly committed to their ethical principles. Likewise, officers who utilize a comprehensive wellness program, including strategies to boost resilience, will be far less likely to experience lapses in ethical decision-making (see Blumberg, Papazoglou, & Schlosser, in press). Further recommendations for action and implication of this matter in law enforcement are presented and discussed.